Megadunes in Antarctica: migration and evolution from remote and in situ observations - Giacomo Traversa; Davide Fugazza; Massimo Frezzotti (2022)
Megadunes are peculiar snow dune fields known to be present only on the East Antarctic plateau and other planets (Mars and Pluto). Antarctic megadunes are climatically important because their leeward flanks are characterized by glazed surfaces, a particular morphogenetic state of snow which makes these zones ablation areas, as their surface mass balance is near-zero or negative, on a continental ice sheet where surface mass balance is on average positive. This work builds on previous efforts in this field and by taking advantage from the most recent remote-sensing products and techniques coupled with field data, aims to provide new information and confirm previous hypotheses about megadunes. Focusing on two sample areas of the East Antarctic plateau where in the past international field activities were carried out (EAIIST and It-ITASE), we analysed the dynamic parameters of megadunes, their albedo and morphology. For the first time we provide a detailed analysis of their upwind migration, in all its components (absolute, sedimentological and ice flow) from remote and field observations, finding absolute values of approximately 10 m a−1 and demonstrating the upwind migration of dune windward flanks, with a relative stability of the leeward faces. Using remote sensing, we analysed their optical characteristics, i.e., albedo (broadband and NIR), brightness temperature and topographic parameters, including slope, aspect and slope along the prevailing wind direction (SPWD). First numerical results about glazed-surface albedo are thus provided, which is found to be lower than the surrounding snow, especially in NIR wavelengths. This detailed information allowed us to perform a precise mapping of glazed surfaces and their evolution and trends over time, demonstrating a general overall intra-annual areal decrease in summer (−16 %) and an inter-annual increase over recent years (at maximum almost +0.2 % per year in January).